PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN - Fransiska Ekobelawati (Jurnal Ekonomi STIEP, 2018)
This research aims to know the influence of Knowledge Management onemployee performance on PT. Anzon Toyota Pontianak and to find out where Knowledge Management indicators that are most influential on employee performance. This research uses the IBM SPSS statistics application. The population in this research are the employee of PT. Anzon Toyota Pontianak. The sample used 40 respondents with using the saturated sample. Technique of data analysis in this research used simple linear regression analysis. Results of the study show that there is influence between variable Knowledge Management which consists of three indicators, namely Personal Knowledge, Job Procedure, and technology on employee performance with determinant of coefficients is 0.256. Data analysis showed that the Personal Knowledge is the indicators with the most biggest influence compared to other indicators.